Interactive techniques to improve speaking skills for eighth year students at ecuela de educación básica Teodoro Wolf, Santa Elena, province of Santa Elena, school year 2015-2016. - Álava López, Magdalena (2016)
This work has been done through an analytical research and shows that interactive techniques are important in schools for the development of speaking skills. Applying various interactive techniques inside and outside the classroom contributes to improve the speaking skills, these techniques motivate the students to learn without feeling uncomfortable or afraid to talk. The activities include games in the schoolyard, pictures and prizes for the winner to promote the development of speaking skills. This project proves that working in groups is very significant, because the students lose fear to speak supporting each other with words and ideas allowing them to participate in an interactive way and causing no boredom in them, transforming the English learning in a dynamic and fun class. This proposal contains activities for the first Quimestre in which students learn how to introduce themselves, how to introduce their best friend in accordance with the goals of the Ministry of Education for students of eighth year. Also it shows that with a little creativity by teacher, he can create a lot of interesting techniques to apply and improve the speaking skill in class.